Community Perceptions of Early Marriage: An Analysis of the Consequences and Impacts of Early Marriage in Pekalongan City - Hayati, Nur (Qanun: Jurnal Hukum Keluarga Islam, 2025)
Marriage is a form of worship in Islamic teachings that is carried out through the process of a marriage contract between a man and a woman. However, in recent years, the phenomenon of early marriage has again stolen the public's attention due to the increasing number of requests for marriage dispensation for minors. One of the reasons for getting married young is to avoid promiscuity and protect the honor of the family. This study aims to examine the determination and consequences of early marriage in Pesindon Village, West Pekalongan. The research method used is a qualitative research method, with data collection through observation, interviews, and documentation. The results of the study indicate that early marriage is considered normal by the local community, with the note that the readiness of the couple must be considered. In fact, the consequences of getting married at a young age are very high, such as financial, mental, and biological risks. However, this can be overcome through the support of family and society which play an important role in creating harmonious early marriages and preventing divorce. This study concludes that understanding the local context and social support is very important in understanding the dynamics of early marriage.